Disciplining Culture Management of Middle School Students in the Eastern of Indonesia - Sherly Ersinta Lawa; Bambang Budi Wiyono; Achmad Supriyanto (Pascasarjana UM, 2019)
Abstract: This study aims to determine the management process of disciplining the culture of high school students. This study used a descriptive qualitative design with a multi-site study design. Col-lecting data through observation, interviews, and documentation studies. Data were analyzed by stages of data condensation, data display, and conclusions, verification. The results of the study show that: (1) discipline of students emphasizes time discipline, dressing, appearance; (2) discipline is applied so that students can become quality and superior people; (3) discipline is built by disseminating rules and sanctions for violations, cooperation with parents; (4) the strategy of building a culture of discipline is to enforce order, punishment, morning ceremonies, spiritual activities; (5) constraints faced by per-sonal learners and parents, the solution taken is to provide guidance and punishment for violating stu-dents, as well as building good cooperation and communication with parents; (6) the results of the im-plementation of disciplinary culture have gone well.Key Words: discipline cultures, middle school students, Sumba cultureAbstrak: Penelitian ini bertujuan untuk mengetahui proses manajemen budaya pendisiplinan peserta didik di Sekolah Menengah Atas (SMA). Rancangan kualitatif deskriptif desain studi multi situs digunakan dalam penelitian ini. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi. Data dianalisis dengan tahapan kondensasi data, display data, dan kesimpulan, penarikan/verifikasi. Hasil penelitian menunjukkan bahwa: (1) pendisiplinan peserta didik ditekankan pada disiplin waktu, berpakaian, berpenampilan; (2) disiplin diterapkan agar peserta didik dapat menjadi insan berkualitas dan unggul; (3) disiplin dibangun dengan mensosialisasikan tata tertib dan sanksi pelanggaran, kerjasama dengan orang tua; (4) strategi membangun budaya disiplin ialah memberlakukan tata tertib, hukuman, apel pagi, kegiatan kerohanian; (5) kendala yang dihadapi dari pribadi peserta didik dan orang tua, solusi yang dilakukan, yaitu memberikan pembinaan dan hukuman bagi peserta didik yang melanggar, serta membangun kerja sama dan komunikasi yang baik dengan orang tua; (6) hasil penerapan budaya pendisiplinan sudah berjalan baik.Kata kunci: budaya disiplin, siswa SMA, budaya Sumba